ACCESSIBILITY OF TRANSPORT SYSTEMS IN PASSENGER TRANSPORTATION - Matiychyk, O.; Kryshkevych, K. (Science-based technologies, 2013)
The given article considers the issue of accessibility of transport systems as a transport indicator having an effect on the integration of transport systems. The level of accessibility of national transport system was proved to reflect the degree of its integration. Factors influencing accessibility of transport are regarded. The factor of inaccessibility was related to a number of constraints. A system of measures for providing transport accessibility was suggested and the indicators of accessibility evaluation showing the degree of access to transport systems on the local and regional level were grouped. Recent trends in evaluating accessibility of transport were regarded. Methods of evaluating accessibility of transport systems were stated. Rational usage of results of accessibility evaluation was recommended to be efficient in solution of transportation problems, optimal planning of transport systems and encouraging social and economic policies towards equal opportunities of economically disadvantaged and physically disabled population in passenger transportation.